2021
DOI: 10.1002/jac5.1502
|View full text |Cite
|
Sign up to set email alerts
|

Medication therapy problem documentation and reporting: A review of the literature and recommendations

Abstract: Pharmacists are increasingly using medication therapy problem (MTP) metrics to monitor their clinical impact and demonstrate their value to health care organizations and commercial payers. Although the practice of documenting and resolving MTPs is well reported in the literature, there remains great diversity in how MTPs are categorized, documented, and reported. We conducted a review of the literature to gain key insights into the MTP classification systems, methods of MTP documentation, and MTP-related outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…These resolution rates are comparable with the literature on MRPs resolved with traditional in‐person CMM, which typically ranged from 49% to 100% 37,38,39 . The heterogeneity in MRP reporting and resolution highlights the importance of specificity and standardization to compare intervention strength 40,41 . Importantly, one study found significantly fewer identified and resolved MRPs in telehealth versus face‐to‐face contact 33 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These resolution rates are comparable with the literature on MRPs resolved with traditional in‐person CMM, which typically ranged from 49% to 100% 37,38,39 . The heterogeneity in MRP reporting and resolution highlights the importance of specificity and standardization to compare intervention strength 40,41 . Importantly, one study found significantly fewer identified and resolved MRPs in telehealth versus face‐to‐face contact 33 .…”
Section: Discussionsupporting
confidence: 66%
“…37,38,39 The heterogeneity in MRP reporting and resolution highlights the importance of specificity and standardization to compare intervention strength. 40,41 Importantly, one study found significantly fewer identified and resolved MRPs in telehealth versus face-to-face contact. 33 The authors hypothesized the difference to be the inability to obtain remote patient monitoring data, time and resource constraints, and gaps in patient digital literacy.…”
Section: Humanistic Outcomesmentioning
confidence: 99%
“…A focus on upgrading documentation systems or rearranging workflow may be needed to replicate results. Using a standardized method of documenting MRPs may allow for multiple pharmacies’ data to be analyzed and provide insight into the pharmacist’s role in patient care [ 30 ]. Research should also continue to explore the prescriber acceptance rates and the factors that impact the acceptance rates.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout their didactic and experiential training, pharmacy students are expected to identify and resolve medication therapy problems (MTPs) 16 . MTPs are events involving pharmacotherapy requiring pharmacist interventions to improve patient outcomes 17,18 . The Pharmacy Quality Alliance (PQA) MTP Categories Framework is the most recognized system to categorize MTPs in clinical practice and to teach the Pharmacist Patient Care Process 17,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…MTPs are events involving pharmacotherapy requiring pharmacist interventions to improve patient outcomes 17,18 . The Pharmacy Quality Alliance (PQA) MTP Categories Framework is the most recognized system to categorize MTPs in clinical practice and to teach the Pharmacist Patient Care Process 17,19,20 . Conway et al and Douglass and Ahmed reported on MTPs in disease management and capstone courses but neither utilized SPs 21,22 …”
Section: Introductionmentioning
confidence: 99%